All species are important, but some species are more important than others. (July 2017) - Ellison, Aaron M.; Degrassi, Allyson L.
Abstract: Foundation species control biodiversity and ecosystem processes, but are difficult to identify. In this issue of the Journal of Vegetation Science, Elumeeva et al. show that Festuca varia and Nardus stricta act as foundation species in the Caucasus' alpine. This paper augments the piecemeal literature on foundation species while highlighting the need for more comprehensive approaches to their identification and conservation. Abstract : Foundation species uniquely control biodiversity and ecosystem processes. In this issue, Elumeeva et al. illustrate the irreplaceability of Festuca varia and Nardus stricta in the Caucasus' alpine. Their exemplary long‐term experiment illustrates challenges inherent in identifying foundation species. We argue that accurate identification and successful conservation of still‐common foundation species requires more than the piecemeal accretion of further case studies.